(untitled) (Indian Journal of Animal Production and Management, 2014)
An experiment was conducted to evaluate the response of laying Vanaraja hens to dietary supplementation of probiotic (Improval) for 7 months. A total of 200 Vanaraja layers at 24 weeks of age were randomly divided into two groups with four replicates of 25 birds in each and reared in deep litter system under standard management systems. It was distinct from the results that dietary inclusions of probiotic had significant effect (P<0.05) on feed consumption, feed conversion ratio, hen day egg production and hen housed egg production. The different egg quality traits viz. egg weight (g), shape index (%), yolk index, Haugh unit and shell thickness (mm) showed significant (P<0.05) improvement over the control groups. Lower mortality of layers was recorded in probiotic supplementation groups (3.38±0.77) compared to control groups (6.29±1.16). Therefore, Improval could be recommended as feed supplement to enhance productive performance and to improve egg quality and health status of laying Vanaraja hens.